Perceptions of farmer group members towards the implementation of the vegetable alley in Yogyakarta city - Sriyadi; Aulina, Finka; Hanifah, Nurul; Hamdzah, Nor Lailatul Azilah (2023)
Yogyakarta City is one of the areas that implements vegetable alleys to meet people s food needs. However, in its implementation there are obstacles to the lack of participation of farmer group members. The study aims to determine the perception of the members of the farmer group towards the implementation of the vegetable aisle, and the factors related to the perception of the members of the farmer group towards the implementation of the vegetable aisle. The research was conducted in the Districts of Umbulharjo, Danurejan and Kotagede. In each sub-district, 4 farmer groups were taken and each farmer group was taken by 5 farmers so that a total of 60 respondents. Data obtained through interviews with a questionnaire. Data analysis used descriptive analysis and spearman rank correlation analysis. The research results show that the perception of farmer group members towards the vegetable aisle from technical and economic aspects is quite good, while from health, aesthetics and environmental aspects it is good. It is recommended that members of farmer groups participate more actively in the implementation of vegetable aisles.